THE PEDAGOGUE-COACH AS A DETERMINANT FACTOR OF FOOTBALL TALENT DEVELOPMENT - Diána DÉRI (Cluj University Press, 2015)
Background: By the 1990's a drastic decline of the general quality of football was experienced in Hungary which called for urgent actions in the field of talent development. Decision-makers realized that the development of more technically proficient home-grown players would be in everyone's best interests. Objectives: The aims of the study are the following: 1. to overview the evolution of the Hungarian Football Development Program; 2. to present the unique features of a youth football club participating in the Program as an example of good practice; 3. to examine the importance of coaches as educators of players. Methods: A qualitative research methodology has been applied in the study. Access was gained to archive sources (decrees, acts, accounts, committee meeting reports) related to state-aid of football talent programs which were examined through document analysis. The study also applied several in-depth interviews with those persons who had key roles in implementing the OTP Bank Bozsik Program in a football club through a fusion (N=5). Results and conclusions: The most important outcome of the predecessors of the OTP Bank Bozsik Program was that they gave a mass base for the selection of football talent which served the development of Hungarian football in the long run and also focused on coaches' education and professional development. The results also confirmed me that bigger emphasis must be put on the pedagogical knowledge learned within the football coach training.